2011
DOI: 10.1111/j.1365-2648.2011.05835.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of the Treatment Adherence Questionnaire for Patients with Hypertension

Abstract: The questionnaire was a brief and psychometrically sound instrument to evaluate hypertensive patients' treatment adherence and to be applied in the research and clinical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 20 publications
0
51
3
Order By: Relevance
“…In China alone, approximately 200 million people suffer from hypertension [1]. Although various therapeutic antihypertensive drugs have been developed to treat and reduce blood pressure, the complications associated with hypertension are harder to treat and remain mostly intractable in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…In China alone, approximately 200 million people suffer from hypertension [1]. Although various therapeutic antihypertensive drugs have been developed to treat and reduce blood pressure, the complications associated with hypertension are harder to treat and remain mostly intractable in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [66] developed and tested the Treatment Adherence Questionnaire for Patients with Hypertension (TAQPH). The TAQPH consists of six subscales with 28 items.…”
Section: Treatment Adherence Questionnaire For Patients With Hypertenmentioning
confidence: 99%
“…The Cronbach's alpha coefficient of the overall questionnaire was 0.86 and 0.82 for test-retest reliability. The authors concluded that the TAQPH can be applied for research and clinical purposes [66].…”
Section: Treatment Adherence Questionnaire For Patients With Hypertenmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is now considered a major public health issue [1] that affects nearly one billion people worldwide [2]. It is recognized as the leading contributor to death and disability globally [3], and the prevalence is dramatically increasing [4,5].…”
Section: Introductionmentioning
confidence: 99%